1985
DOI: 10.1002/aic.690310707
|View full text |Cite
|
Sign up to set email alerts
|

A study of inertial effects in granular bed filtration

Abstract: The filtration efficiency of a granular bed filter was investigated in the domain where inertial effects are dominant. A filtration model predicting single sphere and total bed efficiencies based on trajectory calculations of dust particles in the voids of the granular bed was developed. The model uses the flow field in a bed of spheres arranged in a body-centered cubic array for which the filtration efficiency was found to be a function of a modified Stokes number defined by Sf' = St X F where the function Fd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…The more recent experimental work of Gal et al (1985), however, shows that quite different single-collector efficiencies were obtained using air and helium as carrier gases at identical conditions. Since the viscosities of helium and air are similar but the density of helium is only one-seventh that of air, the observed differences in the single-collector efficiency can only be explained through the Reynolds number.…”
Section: Nk04"'mentioning
confidence: 99%
See 2 more Smart Citations
“…The more recent experimental work of Gal et al (1985), however, shows that quite different single-collector efficiencies were obtained using air and helium as carrier gases at identical conditions. Since the viscosities of helium and air are similar but the density of helium is only one-seventh that of air, the observed differences in the single-collector efficiency can only be explained through the Reynolds number.…”
Section: Nk04"'mentioning
confidence: 99%
“…In recent years a number of investigators have reported results on collection efficiency in granular beds : Thambimuthu, 1980;D'Ottavio and Goren, 1983;Gal et al, 1985;Walata et al, 1986;Takahashi et al, 1986. Without exception, these investigators used commercially available particle counters to measure concentration.…”
Section: and E Are Related By The Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single collector efficiency of a granular filter is defined as the ratio of the number of captured particles to the number of particles introduced in a single collector (Gutfinger and Tardos 1979;Alvin et al 1991;Kuo et al 2010). The total collection efficiency, E, is an exponential function of the physical properties, namely: filter thickness (L), powder size (d c ), porosity (s), and total single collector efficiency (h T ), as expressed in Equation (3) (Allen and Raabe 1985;Gal et al 1985;Kuo et al 2010):…”
Section: Filtration Performancementioning
confidence: 99%
“…Among the several models that have been used for aerosol filtration studies, only the dense cubic packing model has been found to give good results on deposition rates (Gal et al, 1985). The structure of this model and its flow field expressions are, however, too complex to be used in simulation.…”
Section: Selection Of Porous Media Modelmentioning
confidence: 99%